Proton-conduction photomodulation in spiropyran-functionalized MOFs with large on–off ratio. Issue 5 (2nd January 2020) - Kanj, Anemar Bruno; Chandresh, Abhinav; Gerwien, Aaron; Grosjean, Sylvain; Bräse, Stefan; Wang, Yuemin; Dube, Henry; Heinke, Lars
Abstract : A spiropyran functionalized metal–organic framework is presented, allowing to photomodulate the aqueous proton conductivity by two orders of magnitude. Abstract : Proton conduction in nanopores is important for applications in fuel cells, chemical sensors and information processing devices inspired by nature. Here, we present a nanoporous material, a metal–organic framework (MOF) thin film, allowing photomodulation of the aqueous and alcoholic proton conduction of the guests by almost two orders of magnitude. The MOF film possesses spiropyran groups which undergo reversible UV-light induced isomerization to the merocyanine form, a highly polar, zwitterionic molecule, where the strong binding of the guests to the merocyanine isomer efficiently suppresses the proton conduction. Such materials with photomodulated ionic conduction contribute to the development of advanced, remote-controllable chemical sensors and to switchable devices interfacing with biological systems.